Students’ Perception of Declining Learner’s Enrollment in Mathematics : A Context of Universities in Nepal (INTELLIGENCE Journal of Multidisciplinary Research, 2023)
The students' perception of declining learner enrollment at higher levels of mathematics is one of the significant factors to deal with them successfully. Therefore, this study aims to investigate the bachelor second-year students' perception of difficulty in subject matters, the attitude of teachers, the efficiency of subject matters and teaching methodology, the application of mathematics, and existing exam patterns. This investigation is based on the survey research design consisting of 198 respondents of mathematics of second-year students that includes 108 male and 90 female students from different colleges in Pokhara valley. A five-point Likert- scale survey questionnaire, related to independent variables was prepared with 22 structured questions and administered by the researcher to the students. This study used a descriptive research design, where the data were collected and analyzed. The finding of this study concludes that declining student enrollment in higher levels in mathematics was significantly positively correlated with the difficulty in subject matters, attitude of faculty members, efficiency in subject matters, application of mathematics, and existing exam patterns. The study also revealed that most learners positively believe that mathematics was relevant to further studies as it supported to the development of the creative, imaginative, logical, and constructive skills of learners. However, most of the respondents realized that mathematics educators did not support the weakness of learners' problems properly, and most teachers had insufficient skills to connect mathematics knowledge to learners' real lives.